Theory and practice of creativity: challenges of the "pandemic times" - I. V. Zhyvohliadova, (Ukrainian Cultural Studies, 2021)
The article is devoted to the analysis of the problem concerning adapting the art world to the challenges of the global crisis of co-creation caused by the current pandemic situation. The study is based on the understanding that in these extraordinary circumstances the co-creation  becomes an effective form of cultural resistance to social distance. The times of "crisis creativity" is analyzed, which becomes not just a time of "responses" to external challenges that have been accumulated for years, but a time of self-organization, self-ordering of the art world (museums, art galleries, art industry, creativity of individual artists). The analysis of the collective efforts of world museums to maintain the world of art through the creation of forms and methods of artistic communication is made.
Keywords: "pandemic times", the world of art, contemporary creative museum practices, co-creation, artistic communication, culture of perception